The Effect of Assessment Techniques on EFL Learners’ achievement in TOEFL Test (Journal of the College of Education for Women, 2019)
While many educators are highly focused on state test, it is important to consider thatover the course of a year, instructors can build in many opportunities to assess how learnersare learning. Therefore, assessment techniques are considered a good method to get benefitfor both instructors and learners in the process of teaching and learning. The sample consistsof 27 learners who participated in TOEFL training course in the Development and ContinuousEducation Centre. Validity and reliability were verified.To fulfill the aims and verify the hypothesis which reads as follows” It is hypothesizedthat the TOEFL learners' scores will not be increased after TOEFL course training.” T-testfor two dependent samples is used to obtain the results. The analysis of the results shows thatthe learners’ score in posttest and TOEFL ITP test is better than pretest. In the light of theresults, several conclusions, recommendations and suggestions for future study have beenmade.